Writers of Bosnia and Herzegovnia in the Albanian Language: The Antology “Storytellers of Bosnia and Herzegovnia” (4th International Balkan Studies Congress Proceedings, 2025)
The Balkan Peninsula contains dynamic linguistic, cultural, and lite-rary manifestations. We discuss Albanian, Serbian, Bosnian, Macedonian, Bul-garian languages and literatures, among others. Despite this natural dynamism and the linguistic differences, the Balkan region, due to its shared historical, po-litical, and social experiences, forms a common backdrop. This does not imply unification but rather the interaction of diversities within a shared space. Such interaction can be observed, for instance, in the literary themes that various aut-hors from the region address in their works. Thus, Homo-Balcanicus can gain a more comprehensive existential portrait by exploring the works of different authors from this region. The encounter with The Other—or what lies beyond Me—can be achieved either through a shared language or through interlingual translation. The former is less widespread, while the latter is more dominant. Understanding others through language involves translation, where the transla-tor plays a crucial role not only linguistically but also culturally. Encountering ot-hers through translated literature means gaining a better understanding of both them and oneself, and also dispelling prejudices that arise from ignorance. The focus of our paper will be the translation of works by writers from Bosnia and Herzegovina into the Albanian language, aiming to provide an overview of these translations during the 20th and 21st centuries. In our analysis, we will concent-rate on notable figures such as Ivo Andrić and Meša Selimović, among others.